2015
DOI: 10.1016/j.matchemphys.2015.04.056
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous quantum dot-sensitized nanoporous film for hydrogen production under visible-light irradiation

Abstract: To develop the efficient photocatalytic hydrogen production device, tin monosulfide (SnS) quantum dots (QDs) were deposited onto a nanoporous TiO 2 electrode by the successive ionic layer adsorption and reaction (SILAR) method. When Pt nanoparticles as cocatalysts were modified at the interface between the electroconductive glass substrate and nanoporous SnS QDs/TiO 2 layer, hydrogen molecules were produced under visible-light irradiation without applying a bias potential. In addition, the size and color of Sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
(52 reference statements)
1
6
0
Order By: Relevance
“…For example CoS x QDs have been integrated into TiO 2 spheres increasing H 2 production 35-fold to 838 μmol g –1 h –1 . Similarly QDs can be integrated into TiO 2 films, , nanorod and nanotube arrays, , and molecular sieves . A slightly different approach utilized hematite as the photoelectrode since it is a porous material with a medium band gap between QDs and TiO 2, which can potentially improve charge transport in the system and increase overall H 2 production .…”
Section: Related and Miscellaneous Structures/processesmentioning
confidence: 99%
“…For example CoS x QDs have been integrated into TiO 2 spheres increasing H 2 production 35-fold to 838 μmol g –1 h –1 . Similarly QDs can be integrated into TiO 2 films, , nanorod and nanotube arrays, , and molecular sieves . A slightly different approach utilized hematite as the photoelectrode since it is a porous material with a medium band gap between QDs and TiO 2, which can potentially improve charge transport in the system and increase overall H 2 production .…”
Section: Related and Miscellaneous Structures/processesmentioning
confidence: 99%
“…We loaded SnS QDs onto mesoporous TiO 2 electrodes using the successive ionic layer adsorption and reaction (SILAR) method, 29,30 and SnS 2 particles were loaded onto TiO 2 electrodes using a hydrothermal reaction. 31 Detailed experimental procedures are described in the ESI.…”
mentioning
confidence: 99%
“…Since the bandgap of ZnS (3.6 eV) entirely covers that of SnS (1.5 eV), ZnS was selected as the shell material to (i) convert the QDs to type 1 core/shell structure and (ii) eliminate lattice mismatch [ [29] , [30] ]. The pH was regularly measured and kept at 3 for ideal reaction conditions throughout the shelling process.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to commercial catalysts, SnS exhibits several advantages, including tunability for optimizing the photocatalytic process, enhanced stability for longevity and effectiveness of the QDs over time, and low-cost visible-light-driven photocatalysis [ 14 ]. However, a literature survey has revealed that very few works [ [15] , [16] , [17] ] have been reported on applying SnS QDs for the photocatalytic degradation of Rhodamine 6G. Additionally, to the best of our knowledge, there has been no report on (i) the effect of synthetic solvent on the photoluminescence and absorption behavior of SnS-based QDs and (ii) the effect of ZnS coating on degradation efficiency.…”
Section: Introductionmentioning
confidence: 99%